KAJIAN MOTIF BENDA TEKNOLOGIS PADA GAPURA KOMPLEKS MAKAM SUNAN DRAJAT DAN CANDI TEGAWANGI - Ramadhan, Angga Fajar; Handayaningrum, Warih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Ancient buildings are closely related to the long history of the past. The architectural style of the building and its decorative motifs have a distinctive shape in accordance with the spirit of the era of its creation. The idea of creating styles and forms of decoration took the forms of the surrounding nature and the philosophy of the patrons and local rulers. Some of the many decorative motifs that exist, there are motifs that come from religious values. In addition, the various forms of motifs that exist also have similar forms. The similarities in the shape of these motifs are found in the shape of the motifs of technological objects in the gate of Sunan Drajat's tomb which has Islamic breath with one of the relief panels in Tegawangi Temple which has Hindu-Buddhist breaths. The purpose of this research is to describe the idea of the creation of the two forms of motifs, the factors that cause the similarity of the motive forms and reveal the meaning of the two forms of motifs. This research method uses descriptive qualitative methodology. The approach used in this study uses a historical approach, to reveal the meaning used semiotic theory. The data collection technique is done by conducting literature study, observation, interviews and documentation. The data obtained is then reduced, displayed and analyzed. The results showed that the basic idea of creating the motifs of technological objects in the wooden gate of the tomb of Sunan Drajat and Candi Tegawangi took inspiration from the sacred buildings that had been built previously, namely the form of mosques and temples. The factors causing the similarity of form, namely: (a) cultural interaction; (b) adaptation of the form of the motive; (c) acculturation; and (d) marriage or the establishment of family relationships. The meaning of the two motives is the relationship between humans and the transcendent. Bangunan purbakala lekat kaitannya dengan sejarah panjang dari masa lalu. Gaya arsitektur bangunan dan motif ragam hiasnya memiliki bentuk yang khas sesuai dengan semangat zaman penciptaannya. Ide penciptaan gaya dan bentuk ragam hias mengambil bentuk-bentuk alam sekitar dan falsafah dari patron maupun penguasa setempat. Sekian dari banyak motif ragam hias yang ada, terdapat motif yang bersumber dari nilai religi. Selain itu, dari berbagai bentuk motif yang ada juga memiliki kemiripan bentuk. Adapun kemiripan bentuk motif tersebut dijumpai pada bentuk motif benda teknologis di gapura makam Sunan Drajat yang bernafaskan Islam dengan salah satu panel relief di Candi Tegawangi yang bernafaskan Hindu-Buddha. Tujuan penelitian ini adalah untuk mendeskripsikan ide penciptaan kedua bentuk motif, faktor-faktor penyebab terjadinya kemiripan bentuk motif dan mengungkap makna dari kedua bentuk motif. Metode penelitian ini menggunakan metodologi kualitatif deskriptif. Pendekatan yang digunakan dalam penelitian ini menggunakan pendekatan sejarah, untuk mengungkap makna digunakan teori semiotika. Adapun teknik pengumpulan data dilakukan dengan melakukan studi pustaka, observasi, wawancara dan dokumentasi. Data yang diperoleh kemudian direduksi, display dan dianalisis. Hasil penelitian menunjukkan ide dasar penciptaan motif benda teknologis pada gapura kayu makam Sunan Drajat dan Candi Tegawangi mengambil inspirasi bentuk dari bangunan suci yang telah dibangun sebelumnya, yaitu bentuk bangunan masjid dan candi. Faktor yang menjadi penyebab terjadinya keserupaan bentuk, yaitu: (a) interaksi budaya; (b) adaptasi bentuk motif; (c) akulturasi budaya; dan (d) perkawinan atau terjalinnya hubungan kekeluargaan. Adapun makna dari kedua motif tersebut yaitu hubungan antara manusia dengan yang transenden.